MENINGKATKAN HASIL BELAJAR FISIKA DALAM MATERI GERAK MELINGKAR MELALUI IMPLEMENTASI LESSON STUDY MENGGUNAKAN MODEL KETERAMPILAN PROSES SAINS SISWA MAN 2 PONTIANAK - Suminem, Suminem (Universitas Tanjungpura, 2013)
The implementation of Lesson Study aims to gain an overview of the results of studying physics and materials science students’ motivation in a circular motion. The implementation of lesson study is conducted in three (3) cycles by applying multi-model learning. The data collection tool used was a test, observation sheets and questionnaires for students. The test results showed that the average score of work group is 73. Analysis of the observation sheet shows that there is an increase in the activity of the students indicated by interaction between fellow students and the teacher. Questionnaire analysis showed that 55.6% of students were delighted to learn in the teachers’ teaching technique. As many as 88.9% of the students felt curious with the topics discussed in the next topic. Therefore, it can be concluded that the implementation of lesson study improves learning outcomes and circular motion. For students, this activity can also motivate students to learn. The lesson study activities can improve the models teachers’ skills in designing and implementing learning. Keywords: lesson study, multi-model, circular motion.